2016
DOI: 10.1124/jpet.115.229500
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Effects of Abused "Bath Salt" Constituent 3,4-Methylenedioxypyrovalerone in Mice: Drug Discrimination, Locomotor Activity, and Thermoregulation

Abstract: 3,4-Methylenedioxypyrovalerone (MDPV) is a common constituent of illicit "bath salts" products. MDPV is a chiral molecule, but the contribution of each enantiomer to in vivo effects in mice has not been determined. To address this, mice were trained to discriminate 10 mg/kg cocaine from saline, and substitutions with racemic MDPV, S(1)-MDPV, and R(2)-MDPV were performed. Other mice were implanted with telemetry probes to monitor core temperature and locomotor responses elicited by racemic MDPV, S(1)-MDPV, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 23 publications
8
59
0
Order By: Relevance
“…However, despite engendering significantly different MDPV intakes, we did not observe dose-dependent differences in locomotor stimulant effects following oral consumption of these MDPV solutions. This is consistent with our previous findings using intraperitoneal injections (Fantegrossi et al, 2013; Gannon et al, 2016) where we also observed a relatively “flat” dose-effect function for MDPV-induced hyperactivity in the cool (~20°C) ambient temperature of the telemetry laboratory. Similarly, chronic (10 day) access to the 0.30 mg/mL MDPV solution in a forced-choice setting engendered significant locomotor stimulant effects across the access period, but no systematic upward or downward trends in locomotor activity were observed despite escalation of intake resulting in approximately a 2-fold higher MDPV dose on the last three days of the access period than on the first day.…”
Section: 0 Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, despite engendering significantly different MDPV intakes, we did not observe dose-dependent differences in locomotor stimulant effects following oral consumption of these MDPV solutions. This is consistent with our previous findings using intraperitoneal injections (Fantegrossi et al, 2013; Gannon et al, 2016) where we also observed a relatively “flat” dose-effect function for MDPV-induced hyperactivity in the cool (~20°C) ambient temperature of the telemetry laboratory. Similarly, chronic (10 day) access to the 0.30 mg/mL MDPV solution in a forced-choice setting engendered significant locomotor stimulant effects across the access period, but no systematic upward or downward trends in locomotor activity were observed despite escalation of intake resulting in approximately a 2-fold higher MDPV dose on the last three days of the access period than on the first day.…”
Section: 0 Discussionsupporting
confidence: 93%
“…In vivo studies of rodents trained to discriminate methamphetamine or cocaine have reported that MDPV substitutes for both psychostimulants (Gatch et al, 2013; Collins et al, 2016; Gannon et al, 2016). Similarly, we previously trained mice to discriminate MDPV from saline and reported that 3,4-methylenedioxymethamphetamine and methamphetamine generalize to MDPV (Fantegrossi et al, 2013).…”
Section: 0 Introductionmentioning
confidence: 99%
“…These data indicate the PK properties of MDPV enantiomers are not further complicated by in vivo racemization. Nevertheless, since the pharmacological effects are more potently due to ( S )-MDPV (Gannon et al, 2016; Kolanos et al, 2015), it would be important for investigators to know the chiral purity of both ( R )- and ( S )-MDPV stock reagents before use in experiments.…”
Section: Discussionmentioning
confidence: 99%
“…( S )-MDPV has profound pharmacological activity, while ( R )-MDPV is less potent in mice and rats (Gannon et al, 2016; Kolanos et al, 2015). In human users, ( R,S )-MDPV is often self-administered for a rapid onset of action by intravenous, inhalation, or insufflation routes, or by the oral route which has a slower onset of action and susceptibility to gut and first pass metabolism (Froberg et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research supports the legal restriction of these substances, as their pharmacology and abuse liability are comparable to other abused psychostimulants (Cameron et al, 2013; Baumann et al, 2012). However, only a few published studies have examined the interoceptive effects of MDPV or mephedrone using animal models of drug discrimination (Gannon et al, 2016; Fantegrossi et al, 2013; Gatch et al, 2013; Varner et al, 2013). To date, no published studies have examined the specific receptor mechanisms contributing to the interoceptive stimulus effects of these substances.…”
Section: Introductionmentioning
confidence: 99%